A scientific approach to measure public political participation in Pakistan. Issue 1 (2nd January 2019) - Mangi, Shah Nawaz; Shah, Naimatullah; Ali Soomro, Bahadur
ABSTRACT: Public political participation is an exhaustive subject in the democratic system that is contributing as a tilled land since the birth of democracy. It has a wide range of frequency, but voting is one of the easiest among all forms of public participation. Despite the easiness of voting, Pakistan ranks 164th in terms of voter turnout among 169 countries of the world. The voter turnout of the second largest Muslim democracy and the fifth largest among all the democratic states was recorded as 45.3% in the 2013 general election, which was less than India's (59.4%) and even Bangladesh's (58.2%). More than half of the population in Pakistan does not think it is its duty to cast its vote. The present study is an effort to investigate public political participation through six independent variables: democratic political party, party mobilization, security, accessibility, leadership image and moderating factor citizen distrust, and a useful sample size of 1884 was collected across the country. SPSS version 24.0 was used to measure the data. The results show significant and positive relations among the dependent and independent variables, while citizen distrust negatively moderates the dependent and independent variables of the study.